Renal Artery Stenosis: To Intervene, or Not to Intervene, "That is the Question". Issue 1 (1st October 2013) - Haqqie, Syed S.; Nappi, Anthony; Siskin, Gary; Syed, Nouman A.; Ghate, Ketan; Mathew, Roy O.; Wang, Jeffrey; Sidhu, Mandeep S.; Kumar, Vishesh; Salman, Loay; Merrill, Donna; Akmal, Muhammad UT; et al.
Abstract Renal artery stenosis (RAS) due to atherosclerosis continues to be a major cause of secondary hypertension. It can also lead to renal dysfunction due to ischemic nephropathy. While major clinical trials have emphasized that medical management should be preferred over angioplasty and stenting for the treatment of renal artery stenosis, clinical scenarios continue to raise doubts about the optimal management strategy. Herein, we present two cases that were admitted with hypertensive emergency and renal function deterioration. Medical therapy failed to control the blood pressure and in one patient, renal failure progressed to a point where renal replacement therapy was required. Both patients underwent angioplasty (for >90% stenosis) and stent insertion with successful resolution of stenosis by interventional radiology. Postoperatively, blood pressure gradually decreased with improvement in serum creatinine. Dialysis therapy was discontinued. At 4‐ and 8‐month follow‐up, both patients continue to do well with blood pressure readings in the 132–145/70–90 mmHg range. This article highlights the importance of percutaneous interventions in the management of atherosclerotic RAS and calls for heightened awareness and careful identification of candidates who would benefit from angioplasty and stent insertion.